2021
DOI: 10.3389/fgene.2021.625959
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum of LDLR and PCSK9 Genes Identified in Iranian Patients With Premature Coronary Artery Disease and Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a common, yet underdiagnosed, genetic disorder characterized by lifelong elevated low-density lipoprotein cholesterol levels, which can increase the risk of early-onset coronary artery disease (CAD). In the present study, we screened the nucleotide variations of the LDLR and PCSK9 genes, as well as a part of the APOB gene, in Iranian patients with FH and premature CAD to find the genetic cause of the disorder. Fifteen unrelated individuals with a clinical diagnosis of FH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…LDLR mutations can be classified into five types based on their function and synthesis, including type 1 dysfunction of LDLR synthesis (nonsense mutation and splicing mutation); type 2 defect of LDLR trafficking to the cell membrane (generally in ligand-binding domains or EGF precursor homologous domains); type 3 impaired LDL binding (mainly in ligand-binding domain and homologous domain of EGF precursors); type 4 reduced capacity for receptor-mediated endocytosis (mainly in transmembrane domains and cytoplasmic domains); and type 5 diminished LDLR recycling capacity (mainly in homologous domain of EGF precursor) [ 34 , 35 ]. The new variant reported in the present study is located at LDLR exon 15, corresponding to the O-linked sugar domain [ 36 ]. A previous study similarly found that the O-linked sugar domain might regulate LDLR stability or LDLR release from cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…LDLR mutations can be classified into five types based on their function and synthesis, including type 1 dysfunction of LDLR synthesis (nonsense mutation and splicing mutation); type 2 defect of LDLR trafficking to the cell membrane (generally in ligand-binding domains or EGF precursor homologous domains); type 3 impaired LDL binding (mainly in ligand-binding domain and homologous domain of EGF precursors); type 4 reduced capacity for receptor-mediated endocytosis (mainly in transmembrane domains and cytoplasmic domains); and type 5 diminished LDLR recycling capacity (mainly in homologous domain of EGF precursor) [ 34 , 35 ]. The new variant reported in the present study is located at LDLR exon 15, corresponding to the O-linked sugar domain [ 36 ]. A previous study similarly found that the O-linked sugar domain might regulate LDLR stability or LDLR release from cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of various FH-causing mutations on the disease severity and CVD risk is not clear. Among carriers of LDLR mutations, the ones carrying LDLR-negative mutations were found to be more vulnerable to premature atherosclerosis development than patients with LDLR-defective mutations [ 2 ].…”
Section: Genetic Variables In CV Risk In Fh Populationmentioning
confidence: 99%
“…Although, in some regions, founder effects can affect the statistics; on average, between 0.17% to 0.5% of people suffer from a heterozygous form of the disease. Research shows that homozygous hypercholesterolaemia, which was said to affect 0.001% of the population, turns out to be around three times more common [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of CAD is crucial in Iran due to the increasing incidence of premature CAD in recent years. Sedentary lifestyles, familial CAD, type 2 diabetes (T2D), hyperlipidemia, and smoking are the most frequently correlated risk factors, although the precise involvement of genetic susceptibility factors should not be underestimated in population-based studies 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%